Pengaruh Kemampuan Kerja, Inovasi Pelayanan, dan Disiplin Kerja Terhadap Kualitas Pelayanan Publik di Kecamatan Bojonggede Kabupaten Bogor Provinsi Jawa Barat - Farida, Farida; Purwoko, Dwi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
The phenomenon of the quality of public services in Bojonggede District, Bogor Regency has not met expectations. The research aims to analyze and evaluate the influence of work ability, service innovation, and work discipline toward the quality of public services in Bojonggede District, Bogor Regency, West Java Province, partially and simultaneously. This research uses quantitative research with an explanatory approach. The research population receiving public services in Bojonggede District, Bogor Regency for the period January to early March 2024 was 1467 people, with Slovin (5% significance level) obtaining 314 samples. The data analysis technique uses multiple linear regression analysis techniques. Research results: (1) There was a positive and significant influence of Work Ability toward the Quality of Public Services in Bojonggede District, Bogor Regency, West Java Province, which is accepted with a magnitude of 54.91%. (2) There was a positive and significant influence of Service Innovation on the Quality of Public Services in Bojonggede District, Bogor Regency, West Java Province, which is stated to be accepted with a magnitude of 53.58%. (3) There was a positive and significant influence of Work Discipline toward the Quality of Public Services in Bojonggede District, Bogor Regency, West Java Province, which is stated to be accepted with a magnitude of 38.69%. (4) There was a positive and significant influence of Work Ability, Service Innovation and Work Discipline toward the Quality of Public Services in Bojonggede District, Bogor Regency, West Java Province, which is said to be accepted with an Adjusted R Square influence of 65.7% and the remaining 34.3 % influence of other factors but not researched.